WARNA ISLAM DALAM TEKS KLASIK LAYANG MURSADA PESISIRAN - Ekowati, Venny Indria (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2006)
This article is about a study conducted to describe the visualization ofIslamic colors (or nuances) in Layang Mursada Pesisiran, one of the classical textsresulting from the development of coastal literary work.Layang Mursada Pesisiran, the subject of the study, was written (or,rather, copied from the original) in 1879 and published by Badan Pekerja KongresBahasa Jawa, a working body for a congress on the Javanese language. Themanuscript was edited by Bambang Purnomo and transliterated by Suwarni andRatih Retno Hartati in 2001. The data for the study were obtained by repeated textreading. Words, phrases, and sentences in the text containing Islamic colors werewritten down and analyzed descriptively and referentially by referring to verses inthe Al Quran.Results of the study indicate the occurrence of visualization of Islamiccolors in the form of (1) concept of Allah as God with praised character qualities,(2) belief in the Prophet Muhammad, the Prophet Sulaiman, and KhulafaurRasyiidin, (3) concept of heaven and belief in the non-physical substance ofangels, spirits, and devils, (4) acknowledged presence of social figurescharacteristic of Islam who take care of religious matters such as the pangulu,marbotoh, ketib, and modin, (5) concept of the unbeliever, and (6) commandmentto the unbeliever to pray.Keywords: Islamic colors, Islamic concepts